2018
DOI: 10.1002/pc.24732
|View full text |Cite
|
Sign up to set email alerts
|

Novel high‐density polyethylene‐niobium pentoxide dielectric materials

Abstract: This study for the first time reports the processing and properties of high‐density polyethylene (HDPE) reinforced with niobium pentoxide (Nb2O5) up to 40 wt%. In this work, Nb2O5 was chosen as reinforcement because of its advantageous properties such as good dielectric properties, high temperature stability and excellent biocompatible properties. Almost fully dense HDPE–Nb2O5 composites were prepared via hot pressing route. Both the hardness and dielectric properties of the HDPE increased significantly with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…It is noteworthy that the conformational interconversion could have a significant effect for this unusually large tolerance to higher electric fields. It has been shown that in polymeric materials the ability to withstand high electric fields without an electrical breakdown is due to highly dense packing of molecular species (pure HDPF: 0.957 g/cm 3 ) . All three compounds pack closely in the crystal structure with extensive hydrogen bonding and π-stacking resulting in high density (1.45 g/cm 3 for NBOA , 1.41 g/cm 3 for CBOA , 1.38 g/cm 3 for HBOA (I) , and 1.41 g/cm 3 for HBOA (II) ), which could result in materials withstanding higher electric fields.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is noteworthy that the conformational interconversion could have a significant effect for this unusually large tolerance to higher electric fields. It has been shown that in polymeric materials the ability to withstand high electric fields without an electrical breakdown is due to highly dense packing of molecular species (pure HDPF: 0.957 g/cm 3 ) . All three compounds pack closely in the crystal structure with extensive hydrogen bonding and π-stacking resulting in high density (1.45 g/cm 3 for NBOA , 1.41 g/cm 3 for CBOA , 1.38 g/cm 3 for HBOA (I) , and 1.41 g/cm 3 for HBOA (II) ), which could result in materials withstanding higher electric fields.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Besides, it has been employed in various applications as a result of it surface degradation resistance, wear resistance, creep strength, hardness and so on. [127][128][129][130] However, adopting nano-Nb 2 O 5 as a reinforcing phase in polyimide composites remains a point for future study, which could address most issues by improving the properties of polyimide nanocomposites material either by nanomodification or surface modification for thermal, mechanical, and tribological applications. Thus, this present study recommend the use of SPS technique and Taguchi design model in processing polyimide composites in order to achieve a better bonding and properties.…”
Section: Challenges Of Pi Reinforced Nanocomposites For Mechanical An...mentioning
confidence: 99%
“…Polymers are greatly competing with other engineering materials such as metals, alloys, and ceramics . As an example for low load gear applications, metals are being replaced with polymers, namely, high‐density polyethylene (HDPE), acrylonitrile butadiene styrene, and polyoxymethylene .…”
Section: Introductionmentioning
confidence: 99%
“…Polyethylene (PE) is one of the most important thermoplastic polymers for engineering applications. In view of its good mechanical, tribological, biological, and dielectric properties, these polymers have a wide range of applications such as toys, household ware, plastic containers, sheets, pipes, blow molded bottles, ballpoint pen tubes, underground pipes, insulator applications, gear applications, automobile components, flight interiors, energy applications, bio‐applications, and so forth . In particular, HDPE is used as a protective layer for machinery to protect them from wear .…”
Section: Introductionmentioning
confidence: 99%